Organisational commitment in Malaysian public sector - Syed Zainal Abidin, Sharifah Noraida; Muda, Mohd Shaladdin; Abu Hasan, Fauziah; Mohd Salleh @ Embat, Ahmad Munir (Universiti Utara Malaysia, 2010)
This paper describes a research project that aims to determine the level of civil servants’ organisational commitment and the factors associated with it. The instruments used to measure organisational commitment, empowerment, job characteristics, and organisational communication were adapted from Allen and Meyer (1990), Spreitzer (1995), Hackman and Oldham (1975), and Downs and Hazen (1977). The findings demonstrated that civil servants appeared to have a higher level of affective commitment with mean value of 3.88 compared to continuance 3.58 and normative commitment 2.92. The study also found that civil servants were psychologically empowered in the department with mean value of 3.71, had experienced a variable opportunity in job with mean 3.51 and were reported to be satisfied with the existing communication in the department with mean value of 3.68. Research findings also showed that there is a correlation between organisational commitment (affective, continuance, and normative commitment) with empowerment, job characteristics, and organisational communication variables. The stepwise regression exhibited that empowerment variable is the most dominant predictor of civil servants’ organisational commitment. Meanwhile, organisational communication variable appeared to be the most significant factor to influence civil servants’ affective commitment. Civil servants with continuance commitment were found to be best predicted by empowerment variable. Finally, civil servants with normative commitment tend to be mostly influenced by job characteristics variable.